Optimisation, Econometric and Financial Analysis - Kontoghiorghes, Erricos; Gatu, Cristian (Advances in Computational Management Science, 2007)
Advanced computational methods are often employed for the solution of modelling and decision-making problems. This book addresses issues associated with the interface of computing, optimisation, econometrics and financial modelling. Emphasis is given to computational optimisation methods and techniques. The first part of the book addresses optimisation problems and decision modelling, with special attention to applications of supply chain and worst-case modelling as well as advances in the methodological aspects of optimisation techniques. The second part of the book is devoted to optimisation heuristics, filtering, signal extraction and various time series models. The chapters in this part cover the application of threshold accepting in econometrics, the structure of threshold autoregressive moving average models, wavelet analysis and signal extraction techniques in time series. The third and final part of the book is about the use of optimisation in portfolio selection and real option modelling. .